Effect of Exposure Time on the Microscopic Adhesion of Composite Nano Sisal - Nugroho, Dwi Aji; Syafira, Hanna Nidaa (Universitas Muhammadiyah Yogyakarta, 2024)
Composite resin has three main components: a resin matrix, filler particles (filler), and a coupling agent. The inorganic nature of composite resin filler particles contrasts with the organic components prevalent in tooth structure and some adhesives. Therefore, to increase adhesive, innovative composite materials containing organic fillers are required. The aim is to describe the effect of curing time (20, 30, and 40 seconds) on the microscopic adhesion strength of composite resins containing (a) nano sisal, (b) silane-treated hydroxyapatite nano sisal, and (c) Z350XT nanofiller (control) to dentin. This descriptive study investigated the potential of nano sisal, a sisal fiber-based filler in composite resin, as an alternative to conventional synthetic fillers. Samples were divided into three groups: nano sisal composite (Group A), nano sisal composite with a coupling agent (Group B), and Z350XT nanofiller composite (Group C). Premolar teeth were filled with all three composite groups and cured for 20, 30, and 40 seconds. Standardized samples were then extracted for microscopic adhesion observation via a Scanning Electron Microscope (SEM). SEM images of groups A, B, and C showed a gap in the adhesion between the composite resin and the tooth structure. The smallest adhesion distance in group A was at a curing time of 20 seconds (0.687 μm). Group B had a large adhesion distance at 20 seconds (15.747 μm). The smallest microleakege in group C was at 40 seconds of curing time. It was 0.644 μm. Microscopic examination using SEM reveals the presence of microscopic defects at the interface between the restoration and the tooth structure across all investigated curing times (20, 30, and 40 seconds).